ANALISIS PENERAPAN CREATIVE PROBLEM SOLVING TERHADAP KETERAMPILAN 4C PADA MATERI ALAT REPRODUKSI MANUSIA KELAS IX SMP NEGERI 1 SENGAH TEMILA - Petronila Tiara; Eka Trisianawati; Tesa Manisa (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aimed to describe the implementation of the Creative Problem Solving (CPS) learning model and to analyze students’ 4C skills, namely Critical Thinking, Creativity, Communication, and Collaboration, on the topic of the Human Reproductive System in Grade IX of SMP Negeri 1 Sengah Temila. This research employed a descriptive method with a quantitative approach. The participants were 30 students of class IX E. Data were collected through observation, critical thinking tests, and interviews. The data were analyzed descriptively using percentages and supported by interview analysis using NVivo 15. The results showed that Critical Thinking and Creativity skills each obtained a percentage of 87.5%, while Communication and Collaboration skills each reached 93.75%, all categorized as very good. The critical thinking test yielded an average score of 65.17, with 13.33% of students in the very good category, 46.67% good, 30% fair, and 10% poor. Interview findings indicated that the CPS model supported the development of 4C skills, improved students’ understanding of the material, and increased their engagement in learning activities. Therefore, the Creative Problem Solving model can support the development of students’ 4C skills.